2016
DOI: 10.1007/s10517-016-3357-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of hsa-miR-619-5p and hsa-miR-1184 Differ in Prostatic Benign Hyperplasia and Cancer

Abstract: Peripheral blood plasma profiles of circulating microRNA expression were analyzed in patients with prostatic cancer and benign hyperplasia. In prostatic cancer, significant increase in hsa-miR-619-5p and hsa-miR-1184 microRNA expression and significant decrease in hsalet-7b-5p and hsa-let-7c-5p microRNA expression were observed. The role of the relationship between the microRNA expression and the activities and functions of host genes with introns encoding these microRNA is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…Published studies demonstrate that miR-1184 (expressed at the highest levels in our high-risk cohort), is located on the X chromosome but has not been studied in breast cancer. Circulating levels of miR-1184 are reported to be increased in patients with prostate cancer [ 42 ], but were decreased in breast cancer cases in our cohort. MicroRNA-4423-3p has a role in regulating epithelial cell differentiation [ 43 ], is reduced in lung tumors [ 43 ], and downregulated in rheumatic heart disease [ 44 ].…”
Section: Discussionmentioning
confidence: 73%
“…Published studies demonstrate that miR-1184 (expressed at the highest levels in our high-risk cohort), is located on the X chromosome but has not been studied in breast cancer. Circulating levels of miR-1184 are reported to be increased in patients with prostate cancer [ 42 ], but were decreased in breast cancer cases in our cohort. MicroRNA-4423-3p has a role in regulating epithelial cell differentiation [ 43 ], is reduced in lung tumors [ 43 ], and downregulated in rheumatic heart disease [ 44 ].…”
Section: Discussionmentioning
confidence: 73%
“…Connections between miRNA expression and the development of various diseases have been established. miRNA concentrations change in cancer [8] and cardiovascular diseases [9]. Metabolic perturbations change miRNA concentrations in cells [10].…”
Section: Introductionmentioning
confidence: 99%
“… 20 Significant decrease hsa-let-7c-5p was detected in prostatic cancer. 21 QRT-PCR analysis showed that hsa-let-7c-5p was down-regulated in grade 3 endometrial cancer. 22 Let-7c showed a down-regulated trend in cervical intraepithelial lesions.…”
Section: Discussionmentioning
confidence: 98%